2.3-12 µm tunable, sub-10 optical cycle, ZnGeP2-based OPA directly pumped by a Tm:fiber laser at 1.96 µm and 100 kHz - Baudisch, Matthias; Beutler, Marcus; Gebhardt, Martin; Gaida, Christian; Stutzki, Fabian; Hädrich, Steffen; Herda, Robert; Zawilski, Kevin; Schunemann, Peter; Zach, Armin; Limpert, Jens; Rimke, Ingo (Optics InfoBase Conference Papers, 2018)
We demonstrate the first ZnGeP2-based, femtosecond OPA system driven directly by a Thulium-based fiber-laser system operated at 100 kHz. The OPA delivers mid-to-long-infrared tunable pulses with idler energies up to 2.2 µJ (23% quantum efficiency).
CRIS-Team Scopus Importer:2023-04-20